Krizové řízení Dopravního podniku města Hradce Králové, a. s. - Dušek, Ondřej (Univerzita Pardubice, 2006)
Obsahem této diplomové práce je popsat obecné zásady krizového řízení. Celá práce je zaměřena na podnikání v silniční dopravě, hlavně pak na poskytování veřejné osobní dopravy. Konkrétně je krizové řízení aplikováno na Dopravní podnik města Hradce Králové. Součástí je také uvedení a analýza krizového managementu v Dopravním podniku.

The contents of my diploma work is to describe a common principles of crisis management. The hole work is aiming at bussines in road transport, mainly for providing common personal transport. Concrete, crisis management is application for The City Transport Corporation of Hradec Králové, plc.. Presenting and analysing crisis management is the part of this work as well.
Crisis management of the City transport corporation of Hradec Králové, plc.
Keywords: Transport; transport corporations; crisis managements; Doprava; dopravní podniky; krizová řízení; BOZP; IDS